The Values of Feminism in the Novel Mata Dan Nyala Api Purba by Okky Madasari - Rahma, Yadia; Sarwiji Suwandi; Edy Suryanto (Universitas Negeri Semarang, 2025)
Feminist values refer to the basic principles that underlie the feminist movement and thought. These values emphasize gender equality, justice, and women's empowerment in various aspects of life. This qualitative study analyzes Okky Madasari's novel